PENERAPAN MODEL EKONOMI SIRKULAR DALAM PENGELOLAAN SAMPAH BERBASIS QUADRUPLE HELIX DI KOTA GORONTALO - Junus, Dikson; Napir, Suaib (Universitas Bina Taruna Gorontalo, 2025)
This study aims to identify opportunities and challenges in implementing a Quadruple Helix-based circular economy in Gorontalo City and to design effective and inclusive policies to support sustainable waste management. The research method uses a qualitative approach with descriptive analysis, through primary data collection via in-depth interviews, field observations, and documentation studies. The results of the study show that waste management in Gorontalo City still faces challenges such as a lack of public awareness and improper waste disposal, insufficient budget and operational personnel for waste collection, and a digital system and TPS3R management that are not yet optimal. While the circular economy model has been regulated through waste management policies, it is not yet holistic. The implementation of the circular economy in waste management by the Gorontalo City government is carried out through the provision of waste banks, with 10 waste banks established in 2016 and 106 waste banks in 2019. The circular economy implementation model in waste management based on the quadruple helix approach in Gorontalo City is already in place, utilizing a collaborative approach involving the city government, businesses, the community, and universities. This quadruple helix approach leverages the resources of all parties to maximize waste reduction and management in urban areas, thereby impacting environmental quality, public health, and community income. Therefore, a strong commitment from the Gorontalo city government is required, marked by the existence of regulations or local ordinances on environmental management, the provision of support for waste management activities, and the implementation of waste collection, transportation, disposal, and processing services in Gorontalo City.